Study of Optokenetic Nystagmus in Meniere’s Disease - Davronov U. F.; Normuradov N. A.; Xoʻjamurodov Sh. O. (Journal of Science in Medicine and Life, 2025)
The characteristics of optokinetic nystagmus (OКN) were studied in 20 healthy individuals and 30 individuals suffering from Meniere's disease in remission. The results recorded by the method of electronystagmography at frequency optokinetic stimulation 66,90 156 and field/min. found that in healthy people, the frequency of IPOs, the total amplitude and the speed of the slow phase(sp) nystagmus increases proportional to the increase in the frequency optokinetic stimulation; accordingly, consistently reduced the average amplitude window. In Meniere's disease, OКN indicators are generally characterized by lower values than normal, and an increase in the frequency of optokinetic stimulation is accompanied not only by a more pronounced decrease in the total amplitude indicators, but also by a decrease in the speed of the slow phase of OКN. After the glycerol load and with positive results of the glycerol test, the quantitative indicators of OКN increase in patients, approaching the physiological norm. It is concluded that it is appropriate to study the OКN in Meniere's disease to clarify the stage of the disease and predict the effectiveness of treatment.